Relacionamento no Instagram da Netflix: análise do uso de estratégias digitais a partir das relações públicas - Souza, Priscila Nunes (Brasil, 2020)
This work analyzes the use of digital strategies from Public Relations, by Netflix, on the online platform Instagram. It presents fundamental issues regarding the relationship in the digital sphere, especially from the point of view of the Public Relations area. It seeks to identify communicational characteristics present in publications and highlights the image construction carried out by Netflix from its publications on Instagram. In addition, it points out the digital relationship strategies used by the company to promote the engagement of its audiences. It also highlights the importance of public relations activities in the digital environment.